State formation and identity: Historiographical trends concerning South America's War of the Triple Alliance - Izecksohn, Vitor (History compass, 2019)
The War of the Triple Alliance shaped state formation in the Rio De La Plata Basin during the second half of the 19th century. Historians have long debated how emerging countries could have endured such protracted periods of fighting. Recently, however, historiography has moved away from patriotic and military accounts and towards social and political analyses of civilian responses to the bloodbath. These responses had profound consequences for the fragile regional order postindependence. Paraguay, the loser, suffered unspeakable destruction. However, the political systems of the winners, Brazil, Argentina, and Uruguay, were also challenged as initial popular enthusiasm succumbed to the difficult requisites of war. This paper explores how historians have dealt with political, cultural, and demographic changes as war support and resistance waxed and waned over time in the belligerent countries. The war demanded the utmost sacrifices from civilians and soldiers, and their responses created new national identities throughout the Rio de la Plata Basin.